Value of peripheral blood count for dengue severity prediction - Ralapanawa, Udaya (BMC Res Notes, 2018)
OBJECTIVE: This retrospective study was conducted in 2017 with the objective of evaluating the value of acute phase peripheral blood parameters in predicting dengue haemorrhagic fever (DHF). Patients, who were admitted to Teaching Hospital Peradeniya between January and August 2017 due to dengue illness, were recruited into this study. RESULTS: A total of 515 patients participated in the study. Among them, 333 were DHF patients while 182 patients were managed as DF. There was a significant difference in mean values of platelets and haemoglobin observed during acute phase in non-leakers compared to the patients who progressed to DHF, while no significant difference was observed for white blood cells, neutrophils, lymphocytes and haematocrit values. A significantly higher mean value was observed in white blood cells and hemoglobin in leakers compared to non-leakers during day 5. Mean day 5 platelet value was significantly lower among leakers compared to non-leakers but no significant difference between haematocrit, neutrophil and lymphocyte values were observed. ROC curve performed for acute phase platelet values and haemoglobin values to gain a predictive value for female and male DHF patients and cut off values with high sensitivity and specificity to predict DHF could be obtained for the platelet count. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-018-3505-4) contains supplementary material, which is available to authorized users.